The impact of political dualism on urban governance in Swaziland: A case study of Moneni in the city of Manzini. Issue 4 (2nd October 2017) - Sihlongonyane, Mfaniseni F.; Simelane, Hloniphile
ABSTRACT: The article focuses on the experience of dualism and the challenges that arose in the implementation of the Swaziland Urban Development Project (SUDP) in Moneni, a peri-urban township located on the east of Manzini City. The article draws on the existing body of literature on Swaziland (albeit limited) and on Africa to analyse the implications of dualism within the Tinkhundla political system and its precipitous influence on local urban governance. The first section traces the development of the dualistic character of the Tinkhundla political system through the influence of a Swaziana ideology. The second section explores the paradoxical contradictions of the political system and its impact on urban governance. The third section presents an analysis of these paradoxical contradictions by exploring their impact in the case of Moneni during the implementation of the SUDP. The thrust of the argument is that, despite the various moves of reinventing the Tinkhundla political system, the Swazi customary system has led to the reinforcement and re-inscription of royal supremacy through a Swaziana ideology which sustains the precarious conditions of dualistic development.